Security strategies in the Asia-Pacific the United States' "second front" in Southeast Asia - Tan, Andrew T.H (Palgrave Macmillan, 2011)
After 9/11, the U.S.-led global war on terrorism has intruded into an already complex security environment in the Malay archipelago, home to the world's largest population of Muslims, with the potential to catalyze or unleash further dynamics that could destabilize the region. This book argues that, given the existence of a discrete Malay archipelago security complex, with its security linkages and interactive dynamics, it is a fallacy for the United States to approach this region primarily through the prism of global counter-terrorism. Instead, any strategic policy towards the region needs to be founded upon a deep appreciation of the existing Malay archipelago security complex.